Cloth modeling and animation - House, Donald, 1945-; Breen, David E., 1960- (A K Peters, 2000)
"This book not only gives current methods for simulating cloth's look and behavior, it also provides a solid introduction to the construction and characteristics of cloth and even offers helpful hints on character costuming." "With sections on woven and knit fabrics, behavior modeling, dynamic simulation, cloth appearance models, and current techniques and applications of cloth animation, readers will have in this single volume a comprehensive guide to cloth modeling and animation."